Making Energy-transition headway: A Data driven assessment of German energy startups. (October 2021) - Singh, Mahendra; Jiao, Jiao; Klobasa, Marian; Frietsch, Rainer
Abstract: This paper explores the linkage between ongoing clean energy-transition, technology and business model emergence in the German energy sector. The speed of energy-transition is often led by innovative startups. Startups with innovative products, services, or value propositions are a key indicator, supporting successful energy-transition. Though, commercial databases cover comprehensive details to understand startup's financial activity and stakeholder relation, but without considering their innovation and business activity. Measuring the actual activities of energy startups is pivotal to capture the impact of energy-transition. To put this into perspective, a hybrid approach of data collection combining structured and unstructured data has been proposed in the following work. A list of 240 innovative startups belonging to different categories and technology focus are examined. Furthermore, data-driven analysis is performed over the data collected from multiple sources. Renewable technologies are yet the most preferred technology focus among German entrepreneurs and stakeholders. 24.6% startups are identified in this category followed by 17.5% in energy management and 16.2% in energy storage. The evidence from this study suggests a clear shift in technology and the value proposition of successful innovative startups in Germany. Digitalisation of the energy sector is fostering the development of multi-sided digital platform driven business models. The result suggested that 8.0% of startups have implemented purely platform based services while 15.7% are experimenting with platform business models along with traditional business to business (B2B) and business to customer (B2C) business models. Findings could guide policymakers and federal agencies to provide a vision for future technology and business model adaptation in the German energy sector.